Interplay between Ag and interstitial Mg on the p-type characteristics of Ag-doped Mg2Si: challenges for high hole conductivity. Issue 3 (25th November 2014) - Han, Xiaoping; Shao, Guosheng
Abstract : The formation of linear cluster Ag–Mgint –Ag in the 〈111〉 direction explains the difficulty in achieving high hole conductivity in Ag-doped Mg2 Si. Abstract : Although Mg2 Si has been considered to be a highly promising material for low-cost thermoelectric harvest of waste heat at intermediate temperatures, the great difficulty in doping Mg2 Si into an effective p-type semiconductor poses a major technical barrier against utilizing the material to realize efficient devices. Here we attempt for the first time to elaborate its significantly different responses to n- and p-type doping, through theoretical investigation of the best p-type doped system, the Ag-doped Mg2 Si. Using the Heyd–Scuseria–Ernzerhof (HSE) hybrid functional, we find that fundamentally the p-type characteristics of Ag-doped Mg2 Si tend to be achieved through linear clustering between Ag and interstitial Mg ( i.e. Ag–Mgint –Ag) in the 〈111〉 direction in the Mg2 Si lattice, via strong interactions between donor (interstitial Mg, Mgint ) and acceptor (substitutional Ag) states. Such a donor–acceptor interaction leads to lowered hole concentration, on top of the outcome that the Ag-induced hole mobility is only 10% of the electron mobility in the best n-type material, the Sn-doped Mg2 Si. The current work suggests that it is rather challenging to achieve high hole conductivity in Ag-doped Mg2 Si, unless native defects particularly the interstitial Mg atoms can be avoided during the synthesis stage or eliminated through subsequent equilibration treatment.